Social foresight. Issue 2 (11th May 2015) - Roberto Poli, Dr; Poli, Roberto
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to present the three guiding ideas of the social foresight course, namely, the difference between abstract and concrete futures (i.e. the difference between risk and uncertainty); the three levels of futures studies (forecast, foresight and anticipation); and an overview of the early signs of the incipient shift of human and social sciences from their so-far predominant past-orientation to a new, still unfolding, future-orientation. Design/methodology/approach – This paper is a reconstruction of the guiding ideas that have been used for designing the social foresight course. Findings – As far as anticipation is concerned, the authors' understanding of anticipation is still cursory, and the novelty of the perspective may conceal the difficulty implied by this otherwise refreshingly new vision. The theory is at such an early phase of development that it still lacks a unified conceptual language for theorizing and operationalizing anticipation to facilitate cross-disciplinary conversations. Originality/value – The ability to anticipate in complex environments may improve the resilience of societies under threat from a global proliferation of agents and forces by articulating insecurities through anticipatory processes. However, to achieve this end, the joint expertise and theoretical awareness of both the futurists and the human and social scientists is needed.